Meningkatkan Motivasi dan Hasil Belajar Siswa pada Mata Pelajaran IPS melalui Model Pembelajaran Berbasis Proyek - Galuh Sasi (Pendidikan IPS FKIP ULM, 2023)
The low motivation and learning outcomes of students in social studies subjects at Kanisius Gayam I Elementary School challenge teachers to develop innovative approaches related to models, methods, media, learning resources, and evaluation. This study aims to describe the implementation of a project-based learning model to enhance motivation and improve learning outcomes in grade V social studies at Kanisius Gayam I Elementary School. This study falls under the category of Classroom Action Research and involves thirty fifth-grade students at Kanisius Gayam I Elementary School during the 2022/2023 school year. The research focuses on assessing the impact of the project-based learning model on motivation and learning outcomes in social studies. The research employed various instruments, including observation sheets, student learning motivation questionnaires, and tests. Data analysis involved both quantitative and descriptive qualitative methods. The results of the study are as follows: 1) Efforts to enhance motivation and learning outcomes in fifth-grade students at Kanisius Gayam I Elementary School were made through the implementation of a project-based learning model. The steps involved fundamental questions, project planning, schedule preparation, project activeness and development monitoring, testing results, project evaluation, and project outcomes. 2) The study noted an increase in learning motivation from an initial average of 65.66 to 76.26 in cycle I and a further increase to 83.66 in cycle II. 3) Learning outcomes also showed improvement, with an initial average of 54.82 rising to 62 in cycle I and further increasing to 83.66 in cycle II.